Transformasi Strategis Manajemen SDM Pendidikan Era Digital - Sofiyah, Siti; Satriani, Dina; Asmawati, Yeti; Asriani, Nora; Heryanto, Yanto; Muhit, Abdul; Ramdan, Abdi; Evariana, Dian (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to explore the critical dimensions of HRM transformation within Indonesian educational institutions. This study employs a qualitative approach with a library research design. Data sources were obtained from academic literature (Google Scholar, SINTA, and DOAJ using specific keywords) as well as technical policy regulations related to education management. Data were collected through a systematic literature search and analyzed using content analysis and theoretical synthesis techniques. The results highlight four main pillars of transformation: the integration of AI-based digital ecosystems with a human-in-the-loop approach for efficiency; the implementation of Agile Leadership to navigate the uncertainty of the VUCA era; the adoption of Green Human Resource Management (GHRM) which aligns operational efficiency with environmental sustainability; and placing educator well-being as a primary institutional priority. The study finds that successful transformation depends not merely on technological infrastructure, but significantly on organizational culture readiness and psychological support for educators. In conclusion, the synergy between smart technology, flexible leadership, and a supportive work environment serves as a strategic imperative for sustainably improving the quality of learning in the Society 5.0 era.